Type I interferon signaling in malignant blasts contributes to treatment efficacy in AML patients - Holicek, Peter; Truxova, Iva; Rakova, Jana; Salek, Cyril; Hensler, Michal; Kovar, Marek; Reinis, Milan; Mikyskova, Romana; Pasulka, Josef; Vosahlikova, Sarka; Remesova, Hana; Valentova, Iva; et al. (Cell death & disease, 2023)
While type I interferon (IFN) is best known for its key role against viral infection, accumulating preclinical and clinical data indicate that robust type I IFN production in the tumor microenvironment promotes cancer immunosurveillance and contributes to the efficacy of various antineoplastic agents, notably immunogenic cell death inducers. Here, we report that malignant blasts from patients with acute myeloid leukemia (AML) release type I IFN via a Toll-like receptor 3 (TLR3)-dependent mechanism that is not driven by treatment. While in these patients the ability of type I IFN to stimulate anticancer immune responses was abolished by immunosuppressive mechanisms elicited by malignant blasts, type I IFN turned out to exert direct cytostatic, cytotoxic and chemosensitizing activity in primary AML blasts, leukemic stem cells from AML patients and AML xenograft models. Finally, a genetic signature of type I IFN signaling was found to have independent prognostic value on relapse-free survival and overall survival in a cohort of 132 AML patients. These findings delineate a clinically relevant, therapeutically actionable and prognostically informative mechanism through which type I IFN mediates beneficial effects in patients with AML.
Keywords: výsledek terapie; Tumor Microenvironment; signální transdukce; Signal Transduction; nádorové mikroprostředí; Interferon Type I; protinádorové látky; Humans; interferon typ I; Leukemia, Myeloid, Acute; Antineoplastic Agents; Treatment Outcome; lidé; akutní myeloidní leukemie